2019
DOI: 10.3389/fpsyt.2019.00076
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxytocin in Antisocial Personality Disorders: A Systematic Review of the Literature

Abstract: Background and aims: Antisocial personality disorder is an enduring mental disorder associated with significant disease burden and treatment difficulties. This is apparent within forensic populations. There is growing evidence to suggest that treatment with oxytocin could have some benefit in treating a range of psychiatric disorders. There are no reviews studying the use of oxytocin for patients with ASPD. We aim to present the first literature review on the use of oxytocin in patients with ASPD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
(147 reference statements)
0
7
0
Order By: Relevance
“…Overall, oxytocin had beneficial effects on socially positive and non-criminogenic behaviors, with some studies supporting the opposite fact. Probably these discrepancies had a high dependence on social context [ 92 ].…”
Section: Oxytocin’s Relevance In Mental Disordersmentioning
confidence: 99%
“…Overall, oxytocin had beneficial effects on socially positive and non-criminogenic behaviors, with some studies supporting the opposite fact. Probably these discrepancies had a high dependence on social context [ 92 ].…”
Section: Oxytocin’s Relevance In Mental Disordersmentioning
confidence: 99%
“…The need for pleasant social company is increased after a stressful event, a need that varies depending on which alleles of OXTR are present (Sicorello et al, 2020 ). Anatomically, there are subtle changes in structure and inter-connectivity of hypothalamus and parts of the limbic system, and mutations have been implicated in a range of highly maladaptive, sometimes psychopathic traits (e.g., Israel et al, 2008 ; Tost et al, 2010 ; Dadds et al, 2014 ; Aspé-Sánchez et al, 2016 ; Feldman et al, 2016 ; Gedeon et al, 2019 ; Poore and Waldman, 2020 ). A recent neuroimaging study examining the effect of OXTR alleles on resting-state networks reported that receptor genotype affected connectivity between the right hippocampus, medial prefrontal cortex, dorsal anterior cingulate cortex, amygdala, basal ganglia and thalamus (Luo et al, 2020 ).…”
Section: Oxytocin In Humansmentioning
confidence: 99%
“…The great majority of studies emphasize positive, prosocial behavioral outcomes after exogenous oxytocin administration; however, it is important to emphasize that not all studies describe these effects (Keech et al, 2018 ; Tabak et al, 2019 ; Erdozain and Peñagarikano, 2020 ) and some antisocial outcomes have been reported, including increased competitive and aggressive tendencies, particularly in males (Fischer-Shofty et al, 2012 ; Alcorn et al, 2015 ; Ne’eman et al, 2016 ; de Jong and Neumann, 2018 ; Gedeon et al, 2019 ). Others have also reported differential effects of exogenous oxytocin on women compared to men (e.g., Rilling et al, 2012 , 2018 ; Preckel et al, 2014 ; Feng et al, 2015 ; Chen et al, 2016 ; Bredewold and Veenema, 2018 ; Bartz et al, 2019 ; Xu et al, 2020 ).…”
Section: Oxytocin In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are subsumed under the social anxiolytic effects of OT and might have clinical implications for aggression-prone individuals. Yet, it is unclear whether these findings in predominantly male, healthy, non-aggressive individuals can be transferred to aggression-prone individuals [ 28 ]. There is only one neuroimaging study which tested OT’s effect on threat-specific amygdala reactivity in a clinical sample: In women with borderline personality disorder (BPD), OT normalized increased amygdala activation in response to angry faces [ 29 ].…”
Section: Introductionmentioning
confidence: 99%